We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
112
4
avatar+893 

Can anyone solve this? Answer: 22

 Mar 14, 2019
edited by dgfgrafgdfge111  Mar 15, 2019
 #1
avatar+5635 
+2

 

\(g(3)=1\\ a+b+c = f(1) = f(g(3)) = \\ 2(3^2) - 5(3) + 19 = 18-15+19 = 22\)

.
 Mar 15, 2019
 #2
avatar+893 
+1

Thanks!!!

dgfgrafgdfge111  Mar 16, 2019
 #3
avatar+102355 
+1

f(g(x)  =  f ( x - 2)

 

a(x - 2)^2 + b(x - 2) + c  = 

 

a (x^2 - 4x + 4)  + bx - 2b + c

 

ax^2 - 4ax  + 4a  + bx  -2b + c

 

ax^2 + (b - 4a) x + (4a - 2b + c)     =  2x^2 - 5x + 19

 

a = 2

 

b - 4(2)  = - 5

b = 3

 

4(2) - 2(3) + c = 19

2 + c  = 19

c = 17

 

a + b + c  =   22

 

 

cool cool cool

 Mar 16, 2019
 #4
avatar+893 
0

Thanks!!!!

dgfgrafgdfge111  Mar 16, 2019

12 Online Users